Pengaruh Fraud Hexagon Terhadap Fraudulent Financial Statements Dengan Komite Audit Independen Sebagai Variabel Moderasi - Deyoza Syahrizal Alfarizi; Arif Afriady; Yeti Apriliawati; Yanti Rufaedah (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
This study aims to examine the influence of the fraud hexagon elements stimulus, opportunity, rationalization, capability, ego, and collusion on fraudulent financial statements, with independent audit committee serving as a moderating variable. The data used in this research is secondary data obtained from the annual financial reports of healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sample was selected using purposive sampling method, resulting in 20 companies with a total of 100 observations. The analytical method employed in this study is multiple linear regression analysis. The results indicate that the stimulus variable has a significant effect on fraudulent financial statements, while opportunity, rationalization, capability, ego, and collusion show no significant effect. Moreover, the independent audit committee is proven to moderate the relationship between stimulus and fraudulent financial statements by weakening the effect. However, it does not moderate the relationship between opportunity, rationalization, capability, ego, and collusion and fraudulent financial statements.